2017
DOI: 10.1016/j.ymthe.2016.12.018
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Pseudogene DUXAP8 Promotes Non-small-cell Lung Cancer Cell Proliferation and Invasion by Epigenetically Silencing EGR1 and RHOB

Abstract: Recently, the non-protein-coding functional elements in the human genome have been identified as key regulators in postgenomic biology, and a large number of pseudogenes as well as long non-coding RNAs (lncRNAs) have been found to be transcribed in multiple human cancers. However, only a small proportion of these pseudogenes has been functionally characterized. In this study, we screened for pseudogenes associated with human non-small-cell lung cancer (NSCLC) by comparative analysis of several independent data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 43 publications
5
107
0
Order By: Relevance
“…Interestingly, these processes are closely related to cancer cells proliferation and invasion. As well as our findings, Sun et al24 reported that DUXAP8 promotes cell proliferation and invasion through repressing EGR1 and RHOB expression in human non small cell lung cancer; Ma et al25 found that DUXAP8 promotes cell proliferation through epigenetically silencing PLEKHO1 expression in gastric cancer. In addition, Kong and colleagues27 revealed that LINC00460 facilitates tumorigenesis by sponging miR‐149‐5p to up‐regulate IL6 in nasopharyngeal carcinoma; Liang et al28 reported that LINC00460 expression is upregulated in ESCC tissues and positively correlated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, these processes are closely related to cancer cells proliferation and invasion. As well as our findings, Sun et al24 reported that DUXAP8 promotes cell proliferation and invasion through repressing EGR1 and RHOB expression in human non small cell lung cancer; Ma et al25 found that DUXAP8 promotes cell proliferation through epigenetically silencing PLEKHO1 expression in gastric cancer. In addition, Kong and colleagues27 revealed that LINC00460 facilitates tumorigenesis by sponging miR‐149‐5p to up‐regulate IL6 in nasopharyngeal carcinoma; Liang et al28 reported that LINC00460 expression is upregulated in ESCC tissues and positively correlated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Among these increased lncRNAs, we found that DUXAP8 and LINC00460 are consistently upregulated in TCGA data and three GEO datasets (Figure 4A,B). Interestingly, DUXAP8 has also been reported to be overexpressed in human non small cell lung cancer,24 gastric cancer25 and renal cell carcinoma,26 while LINC00460 expression is upregulated in nasopharyngeal carcinoma27 and promotes carcinogenesis in ESCC 28. Therefore, we chose these two lncRNAs for further analyses and validation.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 genes that were downregulated by TRIM44, three genes were found to possess tumor suppressive functions (Figure A; FRK, EGR1 and BCL2L14 ). We then used the Oncomine dataset to analyze the expression level of these three genes in tumors. FRK was the only gene that showed low expression levels in cancer compared with benign tissues (Figures B,C and ).…”
Section: Resultsmentioning
confidence: 99%
“…5H and I). The transcriptional factor of EGR1 is expressed in response to various extracellular signals such as growth factors, cytokines, irradiation and various kinds stressors and it has been confirmed that EGR1 plays a significant role as a tumor suppressor in breast, brain, and lung cancer and inhibits growth and transformation when overexpressed [42-44]. SEPW1, a mammalian archetype of the selenoprotein W-like family, is an ubiquitous 9 kDa Sec-containing protein with glutathione-dependent antioxidant activity [45] that promotes tumor growth in breast cancer [26].…”
Section: Discussionmentioning
confidence: 99%